Engaging East Asian Integration : States, Markets and the Movement of People - Shiraishi, Takashi (Book collections on Project MUSE., 2012)
Both international trade and investment by East Asian countries have become significantly regionalized. To support this development further, efforts for regional integration have flourished in the forms of bilateral and regional free trade agreements and the ASEAN+3 and East Asia Summit processes, among many others. This book is a compilation of papers and discussions originally presented at the international symposium held during the recent global financial crisis. The symposium aimed to shed light not only on the usual economic aspect but also on other aspects of the multidimensional phenomenon called "regional integration."